Efficacy of immune checkpoint inhibitors combined with bevacizumab in MSS/pMMR advanced colorectal cancer after first-line treatment failure - Chen, Xiaoqian; Li, Wenkui; Lei, Xiaogai; Li, Zhanhong; Guo, Qijing; Ma, Xinfu; Luo, Yushuang; Wang, Liang (Frontiers in Oncology, 2024)
Objective To investigate the effects of a PD-1 inhibitor combined with a bevacizumab monoclonal antibody on tumor immune cells in patients with first-line treatment failure in MSS/pMMR advanced colorectal cancer. Methods Control group consisted of 50 patients treated with the FOLFIRI combined with Bevacizumab regimen. The experimental group consisted of 60 patients treated with the Sintilimab combined with Bevacizumab regimen. By comparing the expression levels of CD8+ T lymphocytes, TAMs, and CAFs before and after treatment, short-term efficacy after treatment, and adverse drug reactions between the two groups, we comprehensively evaluated the impact of Sintilimab combined with Bevacizumab on patients with MSS/pMMR advanced colorectal cancer who failed first-line treatment. Results There was a statistically significant difference in the percentage of CD8+ T lymphocytes, TAMs, and CAFs before and after treatment between the two groups (P<0.05);Immunohistochemical scoring of CD8+ T lymphocytes, TAMs, and CAFs showed significant differences between the groups post-treatment (P<0.05). The experimental group demonstrated statistically significant differences in immunohistochemical scoring of CD8+ T lymphocytes, TAMs, and CAFs before and after treatment (P<0.05). There was a statistically significant difference in the therapeutic effect between the two groups of tumors (P<0.05). The experimental group had greater PFS, mPFS, ORR, and DCR than did the control group. There was no statistically significant difference in the occurrence rate of drug-related adverse reactions after treatment between the two groups (P>0.05). The results of the Cox proportional hazards model analysis indicate that age, gender, and group are independent risk factors affecting MSS/pMMR advanced colorectal cancer patients treated with second-line therapy in this study. Patients aged ≤60 years, male patients, and those in the experimental group showed better treatment responses in this study. Conclusion By administering immune checkpoint inhibitors in combination with bevacizumab to patients with advanced colorectal cancer with MSS/pMMR disease for whom first-line treatment failed, not only did the patients’ prognosis improve, but the adverse drug reactions were also safe and controllable.